Simulation Modelling of Market of Derivative Financial Instruments - Марич, Максим; Bazhanova, Nataliia; Stashchuk, Olena; Shevtsiv, Lyba; Purtskhvanidze, Olga; Tarasova, Olena (My University, 2019)
The complexity and complexity of the derivatives market requires a special approach to analysis and forecasting. To this end, the article discusses the method of simulation of the derivatives market using open-source software. The article describes the approach to creating a model simulating the behaviour of agents in the derivatives market. Possible options for setting parameters and tracking changes in key indicators are described. The model complex for simulating the work of the market of derivatives described in the article is also possible to implement using software methods and implement it in other algorithms, without compromising its functionality. The article describes the modelling of standard situations in the market, however, the flexibility of settings allows you to simulate any necessary task
Keywords: Derivative Financial Instruments; Financial Market; Modelling; Simulation